The founders and the bible - Richard, Carl J. (Rowman & Littlefield, 2016)
A people of the book -- A lifelong passion -- Heroes and villains -- Divine intervention -- The new Israel -- Religion, morality, and republicanism -- Other shared beliefs -- Differences -- Human nature and balanced government -- Church and state